A photovoice study on the bereavement experience of mothers after the death of a child. Issue 5 (28th May 2021) - Kim, Min Ah; Yi, Jaehee; Sang, Jina; Jung, Daehee
Abstract: This study explored the bereavement experience of mothers after losing a child to cancer in Korea, using photovoice. The mothers took photos reflecting five subject areas they selected: (a) if I had one more day with my child, (b) memories with my child, (c) dreaming of my child's healthy future, (d) what gave me strength, and (e) fulfilling my child's wishes for the future. The findings show that mothers who lost a child to cancer need bereavement care to promote well-being. This study can help pediatric oncology providers develop bereavement interventions that address parental grief and improve quality of life.